Copyfight : the global politics of digital copyright reform - Haggart, Blayne (Studies in comparative political economy and public policy., 2014)
To answer this question, Copyfight examines the 1996 World Intellectual Property Organization internet treaties that began the current digital copyright regime. Blayne Haggart follows the WIPO treaties from negotiation to implementation from the perspective of three countries: the United States, Canada, and Mexico. Using extensive interviews with policymakers and experts in these three countries, Haggart argues that not all the power is in the hands of the U.S. government. Small countries can still set their own course on copyright legislation, while growing public interest in copyright issues means that even the United States might move away from ever-increasing copyright protection"--Publisher